The Factors Influence of Students’ English Achievement in the Morning and Afternoon Course Schedule at Seventh Grade of SMP N 12 Solok Selatan - Wati, Nofi Selvia; Syahrul, Syahrul; Eliza, Eliza; Dewi, Merry Prima (Education Achievement: Journal of Science and Research, 2024)
This research related to the factors that influence of students achievement in the course schedule (Morning and afternoon). According to some experts, studied in the morning was more effective than in the afternoon and made the students achievement in the morning better than studied in the afternoon. However, based on the fact found in SMP N 12 Solok Selatan in seventh grade, it showed that average score students' English achievements were almost same between students who studied English in the morning and afternoon. Therefore, the researcher wanted to find out the factors causing there was no difference in students' English achievement results between morning and afternoon classes. Qualitative descriptive was the design in this research. Researcher used observation and interviews as the instrumentation. Seventh grade at SMPN 12 Solok Selatan as informants. To analyze the data, the researcher used the theory of Miles, Huberman, and Saldana. Based on research results, the factors that make students English achievement the same were external factors, namely teacher and lesson standard. The teachers treatment and the way she taught was the same to all students, but when the teacher taught in the afternoon the teacher carried out several activities that made students re-focused and enthusiastic in learning, such as ice breaking and made joked with students. In conclusion, how the teachers taught both in the way they present the material and their creativity in creating learning condition that still conducive at all times, and also how the teachers attitude to students.